2016
DOI: 10.1515/biolog-2016-0095
|View full text |Cite
|
Sign up to set email alerts
|

Studies on eucrenal-hypocrenal zonation of springs along the river mainstream: A case study of a karst canyon in Bosnia and Herzegovina

Abstract: The canyons in Dinaric karst are known to harbour a diverse aquatic fauna living in springs along the river mainstream. However, the knowledge on the ecology of these springs and also on the springs in mountainous areas of the Balkan Peninsula in general is poor. This study is focused on the macroinvertebrate assemblages of three different types of springs along the Cvrcka River (Republic of Srpska, Bosnia and Herzegovina). The aim of this study was to check whether existing criteria for regional spring zonati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

7
2

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…Piscicola hadzii is known only from the Buna River (spring and first-order stream) in southwestern part of Bosnia and Herzegovina (Sket 1985). Dina sketi inhabits few springs in Cvrcka river basin in north-western part of Bosnia and Herzegovina (Grosser et al 2014a;Pešić et al 2016). In this study we have reported this species in the springs and streams of the Crna Rijeka Basin (Table 1), about thirty kilometers southwest of the previously known localities (Figure 1).…”
Section: Discussionsupporting
confidence: 55%
“…Piscicola hadzii is known only from the Buna River (spring and first-order stream) in southwestern part of Bosnia and Herzegovina (Sket 1985). Dina sketi inhabits few springs in Cvrcka river basin in north-western part of Bosnia and Herzegovina (Grosser et al 2014a;Pešić et al 2016). In this study we have reported this species in the springs and streams of the Crna Rijeka Basin (Table 1), about thirty kilometers southwest of the previously known localities (Figure 1).…”
Section: Discussionsupporting
confidence: 55%
“…In most recent studies, springs have been widely recognised as important freshwater sites maintaining high biodiversity, especially in mountainous regions (Pe sić et al, 2016;von Fumetti et al, 2017;Savić et al, 2017). They are inhabited by a number of rare, even endemic species, many of which are spring specialists, the so-called crenobionts (von Fumetti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The lower and usually stable temperature creates optimal conditions for stenothermal cold-water organisms and thus springs can highly contribute to the regional biodiversity of freshwater ecosystems (Boulton 2005;Pešić et al, 2016). Beside the temperature, the macroinvertebrate composition of springs is also influenced by various environmental factors such as hydrological conditions, physico-chemical parameters and substratum composition (Hahn, 2000;Ilmonen and Paasivirta, 2005;von Fumetti et al, 2006;von Fumetti and Nagel, 2012).…”
Section: Introductionmentioning
confidence: 99%